Academic detailing improves identification and reporting of adverse drug events - Schlienger, Raymond; Lüscher, Thomas F.; Haefeli, Walter E.; Schoenenberger, Ronald A. (Pharmacy world & science, 1999)
In a prospective, crossover study, we assessed the impact of a clinical pharmacist on identification and reporting of adverse drug events (ADEs) in hospitalized patients. The study was conducted on four units of a medical ward of a university hospital, with two units serving as test, the other two as control units. After 12 months, test and control units were switched. In the test units, a pharmacist participated in daily ward rounds, solicited additional information from physicians and nurses, and reviewed the charts of all patients. In control units, information on ADEs was based solely on voluntary reports from physicians and nurses. A total of 1959 patients (941 in test, 1018 in control units) were hospitalized during the study period. In 137 test units patients, 224 ADEs (14.6%; 95%‐CI: 12.3%‐16.9%) were detected (8 severe, 60 moderate, 156 mild), while 25 ADEs (1 severe, 11 moderate, 13 mild) occurring in 21 patients (2.1%; 95%‐CI: 1.2%‐3.0%) were reported from the control units (p<0.0001). Of the ADEs in the test units, 51% were reported spontaneously, 39% were identified on rounds, and 10% by chart review. After changing the status of test and control units, the number of identified ADEs returned to preintervention levels. Clinical pharmacists as part of the medical care team can improve the identification of ADEs which may ultimately translate into improved quality of care.